2014
DOI: 10.1111/cas.12484
|View full text |Cite
|
Sign up to set email alerts
|

TET2 as an epigenetic master regulator for normal and malignant hematopoiesis

Abstract: DNA methylation is one of the critical epigenetic modifications regulating various cellular processes such as differentiation or proliferation, and its dysregulation leads to disordered stem cell function or cellular transformation. The ten-eleven translocation (TET) gene family, initially found as a chromosomal translocation partner in leukemia, turned out to be a key enzyme for DNA demethylation. TET genes hydroxylate 5-methylcytosine to 5-hydroxymethylcytosine, which is then converted to unmodified cytosine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 71 publications
(159 reference statements)
1
70
0
1
Order By: Relevance
“…Interestingly, we did not find a correlation of IDH1 mutations and 5hmC amount. As mutated IDH1 (R132H) leads to the production of 2HG, a competitive inhibitor of ten-eleven-translocation (TET) enzymes [31], our data emphasize that in IDH1 wild type, GBMs alternative oncogenic pathways are activated leading to the loss of 5hmC [32,33].…”
Section: Relationship Of 5hmc and Proliferation Markers In Gbms And Imentioning
confidence: 64%
“…Interestingly, we did not find a correlation of IDH1 mutations and 5hmC amount. As mutated IDH1 (R132H) leads to the production of 2HG, a competitive inhibitor of ten-eleven-translocation (TET) enzymes [31], our data emphasize that in IDH1 wild type, GBMs alternative oncogenic pathways are activated leading to the loss of 5hmC [32,33].…”
Section: Relationship Of 5hmc and Proliferation Markers In Gbms And Imentioning
confidence: 64%
“…The Tet2-inactivating mutations in hematological malignancies and other solid tumors suggest that cellular transformation is in part caused by the dysregulation of 5mC conversion (Nakajima and Kunimoto, 2014). It has been suggested that downregulation of Tet2 is responsible for the loss of 5hmC in melanoma cells and overexpression of Tet2 suppresses melanoma growth, indicating that 5hmC regulated by Tet2 affects melanoma progression (Lian et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Its knockdown effects result in loss of 5hmC with a possible concomitant increase in 5-mC. TET2 is a crucial regulator of HSC-homeostasis [64]. TET2 mutations in MDS are thought to result in loss of catalytic activity.…”
Section: Tet2 (4q24)mentioning
confidence: 99%